2020
DOI: 10.1007/s00590-020-02648-9
|View full text |Cite|
|
Sign up to set email alerts
|

Better outcomes after mini-subvastus approach for primary total knee arthroplasty: a Bayesian network meta-analysis

Abstract: Introduction Alternatives to the classical medial parapatellar (MPP) approach for total knee arthroplasty (TKA) include the mini-medial parapatellar (MMPP), mini-subvastus (MSV), mini-midvastus (MMV) and quadriceps-sparing (QS) approaches. The best approach has been not fully clarified. The purpose of the present study was to conduct a Bayesian network meta-analysis comparing these approaches. Materials and methods The present analysis was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…A number of systematic reviews and meta-analyses have investigated the relationship between the SV and MPP approaches [15, [44][45][46][47][48][49][50][51] with some having similar trends to our study. However, the majority of those studies yielded less than 15 RCTs [15,[44][45][46][47][48][49]51] with only one study [50] reporting on 20 RCTs.…”
Section: Discussionsupporting
confidence: 71%
“…A number of systematic reviews and meta-analyses have investigated the relationship between the SV and MPP approaches [15, [44][45][46][47][48][49][50][51] with some having similar trends to our study. However, the majority of those studies yielded less than 15 RCTs [15,[44][45][46][47][48][49]51] with only one study [50] reporting on 20 RCTs.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the surgical approach may influence the clinical outcomes. A recent network meta-analysis demonstrated that the mini-subvastus approach outperformed all other approaches (mini-medial parapatellar, midvastus, quadriceps sparring) [ 77 ]. Patellar retaining or resurfacing has not been investigated, and may represent a further limitation [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Funnel plots were generated to estimate the risk of publication bias by plotting the natural logarithm of an individual study effect size against the standard error of the natural logarithm of an individual study effect size. This methodology has been already used in previous studies [18][19][20][21]. A further meta-analysis comparing subgroups selective vs non-selective NSAID was performed.…”
Section: Discussionmentioning
confidence: 99%